Impact of sperm DNA fragmentation index on assisted reproductive outcomes: a retrospective analysis - Yang, Bin; Xia, Leizhen; Deng, Rufei; Wu, Liping; Zhang, Zhiqin; Wu, Xingwu; Ding, Tao; Zhao, Yan; Huang, Jialyu; Huang, Zhihui (Frontiers in Endocrinology, 2025)
BackgroundThe role of sperm DNA fragmentation index (DFI) in fertility remains controversial. Herein, we analyzed its association with semen parameters, embryonic development, and pregnancy outcomes after in vitro fertilization (IVF) treatment. Additionally, we assessed whether DFI had a potential impact on long-term maternal and neonatal complications.MethodsA total of 5,271 women who underwent IVF treatment for the first time between October 1, 2020, and July 31, 2023, were included from an academic fertility center. Participants were categorized into three groups based on sperm DFI: DFI < 15%, 15 ≤ DFI < 30%, and DFI ≥ 30%. We collected data on patient demographics, semen parameters, embryonic development, clinical outcomes, maternal and infant complications. Multivariate logistic regression analyses were conducted to control for potential confounders.ResultsThe DFI value was negatively correlated with semen quality in males. High DFI affected the blastocyst formation rate (56.44%, 55.32%, 53.72%, respectively; P=0.045) and the rate of transferable embryos (3.97 ± 2.71, 3.90 ± 2.7, 3.38 ± 2.4, respectively; P<0.001); however, no significant difference in pregnancy outcomes was observed among the three groups. Elevated DFI did not contribute to clinically relevant adverse maternal events during pregnancy, but it was associated with an increased risk of low birth weight (3.9%, 6.6%, 10.1%, respectively; P=0.006) in newborns.ConclusionsSperm DFI could influence embryonic development, with a higher risk of low birthweight infants in the high DFI group. However, it does not appear to affect clinical outcomes or other perinatal complications. The role of DFI as a predictive factor in assisted reproduction, especially regarding offspring outcomes, requires further investigation with larger sample sizes.